PEMBUKTIAN SIFAT RUANG BANACH PADA D(K) - Malahayati Malahayati (Universitas Jenderal Soedirman, 2012)
In this paper we study class of all functions which are differences of bounded semicontinuous functions on a separable metric space K denoted by . Haydon, Odell and Rosenthal (1991) proved that is a Banach space by using the series criterion for completeness. In this paper we prove the statement in a different way.